Relation between grip and pinch strength and pitch type in high school pitchers with and without elbow symptoms. (27th January 2020) - Tajika, Tsuyoshi; Oya, Noboru; Ichinose, Tsuyoshi; Shimoyama, Daisuke; Sasaki, Tsuyoshi; Hamano, Takanori; Shitara, Hitoshi; Yamamoto, Atsushi; Sakamoto, Masaaki; Takagishi, Kenji; Chikuda, Hirotaka
Objective: Gripping and pinching a ball is a fundamentally important part of the kinetic chain for throwing baseball pitches of various types. This study of high school pitchers was conducted to assess the association between grip and pinch strength, the pitch type, and the history of elbow symptoms. Methods: We examined 133 high school baseball pitchers, all of whom had completed a self-administered questionnaire including items related to pitch type throwing ratios, the age at starting each pitch type, and throwing-related elbow joint pain sustained during the prior 3 years. We measured grip strength and the bilateral side tip, key, and palmar pinch strengths. Comparisons were made between the participants with and without an elbow symptom history to assess the grip and each pinch strength, throwing ratio of pitch type, and the age at starting to throw each pitch type. Results: Pitchers with an elbow symptom history exhibited less difference between the grip strength on the throwing side than those with no elbow symptom history ( p = 0.04). No difference was found between participants with and without an elbow symptom history in terms of pinch strength, the throwing ratios of pitch types, or the age at starting to throw pitches of each type. Positive significant association was found between pinch strength on the pitching side and the forkball and screwball throwing ratio ( r = 0.27, p = 0.002). Conclusion: Grip strength might influence high school baseball pitcher elbow conditions. The frequency of certain pitch types might develop pinch strength in high school baseball pitchers.